A Pastoral Theological Study Of Faithfulness Tested Through Relational Wounds And Rehabilitation In A Trauma-Informed Perspective - Tintingon, Angel Ribka; Tewu, Peggy Sandra (International Journal of Education, Information Technology, and Others, 2025)
In human connections, loyalty serves as the bedrock, frequently challenged by acts of disloyalty, letdowns, and emotional scars from relationships. Such injuries inflict not just psychological pain but also disrupt one's spiritual equilibrium, leading to a profound loss of confidence in self, fellow beings, and even the divine. From a Christian viewpoint, concepts of fidelity and treachery are framed within the promise of healing through Christ's boundless affection. This investigation seeks to examine the interplay of steadfastness under strain from interpersonal harms and its mending process, guided by a pastoral theology attuned to trauma. Employing a qualitative methodology centered on literary review, information is gathered from scriptural passages, writings on pastoral divinity, insights from trauma psychology, and modern analyses of ecclesiastical practices. Proceeds descriptively and analytically, juxtaposing doctrinal concepts with trauma viewpoints to forge a practical framework for pastoral application. Findings reveal that tested loyalty transcends mere moral concerns, intertwining deeply with the essence of one's belief system. Pastoral theology stresses that mending relational breaches should anchor in unwavering devotion to the Almighty, acknowledging that complete human reconciliation may remain elusive. A trauma-sensitive pastoral strategy proves apt, as it prioritizes establishing secure environments, weaving in elements of devotion and ritual, and viewing absolution as an ongoing journey rather than a swift mandate. Within the Reformed GMIM framework, such relational afflictions are seen as facets of flawed humanity, yet redeemable into avenues for spiritual maturation via divine mercy. Ultimately, this inquiry underscores that authentic renewal surpasses simple interpersonal mending, evolving into a holistic life metamorphosis grounded in the Lord's enduring compassion and reliability.